129k views
5 votes
Solve the simultaneous equation

Solve the simultaneous equation-example-1
User Ialexander
by
5.5k points

2 Answers

5 votes

Answer:

y= -1

x= 2

Explanation:

User Oenotria
by
5.2k points
4 votes
So for these system of equations I'll be using substitution to solve. To be able to do that, however, you'll have to subtract 2x on each side of the first equation to get
y=3-2x .

Now substitute y in the second equation for (3-2x), and then you can solve for x. Your second equation should look like this:
5x-2(3-2x)=12

Multiply -2 and (3-2x) to get
5x-6+4x=12

Combine like terms to get
9x-6=12

Add 6 on each side to get
9x=18, then divide 9 on each side and your answer should be
x=2



Now that we got x, we can just substitute x for 2 in either equation to solve for y.


2(2)+y=3 \\ 4+y=3 \\ y=-1



In short, x = 2 and y = -1.
User Alhuck
by
5.1k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.